If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-8+9-2x=x+3
We move all terms to the left:
3x-8+9-2x-(x+3)=0
We add all the numbers together, and all the variables
x-(x+3)+1=0
We get rid of parentheses
x-x-3+1=0
We add all the numbers together, and all the variables
-2!=0
There is no solution for this equation
| 11=m•50 | | 3(-0.25+-0.75y)-6y=2 | | 5v^2-6v=-6 | | C=20+25x | | x+2=31-11 | | 7c+c=17 | | 6-3=y+2 | | 1/9r=10 | | 3/8r=10 | | 1/9r=40 | | 1/9r=20 | | 8x-16-0x=32 | | 9n-10=3n-18 | | 2x-4(-4x-2)=-118 | | 6/8x=6 | | 5x+3-2x-5-x=-21 | | x*12+24=36 | | 2(n+5)=2£ | | 26/8x=6 | | 5(m+2)=9m-7m+8 | | -12(k+4)=62 | | 79.90+45.99+14.99w=170.86 | | 3(r-2)=16 | | 2x-9=3x-30 | | -3(5x+8+4x-12=-80 | | 16x-52=12 | | 2x-9+3x-30=180 | | -7n-19=-5(n+1) | | 12p=p+14=p | | 3/8r=63 | | x+(x^2)=(7x)^2 | | -2+x=-+2x |